Penataan Ruang Kelas Yang Sesuai Dengan Aktivitas Belajar Kasus: Paud Kuncup Matahari Dan Pg/Ra Mutiara Bhima Sakti Sidoarjo - M., Triandriani; S., Noviani; T., Ema Yunita (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2014)
The main problem of PG/RA Mutiara Bhima Sakti and PAUD Kuncup Matahari’s classroom design is how to optimize the available space-resources to accomodate learning acitivities.This could be a supporting factor to success learning program. This research aim to find the suitable classroom model for PG/RA Mutiara Bhima Sakti and PAUD Kuncup Matahari by studying of space-use and learning program. PG/RA Mutiara Bhima have only 1 permanent classroom, while another classroom was divided into 2 classrooms using non-permanent divider. PAUD Kuncup Matahari’s classroom was too small to accomodate all the students. From the result of the analysis and according to BCCT program (as the learning program used by those two prescools), we arrange classroom into centers: natural, dramatic, preparation, block, etc. These centres was arranged by utilize space-resources optimizely. One centre colud be used by one class or more, in the same time or in different time. The classrooms was designed flexible. They can be used for different activities by changing their interior arrangement.Kata kunci: arrangement, classroom, children